Comparative Study of Iron and Steel Industry Transition in the Countries of Central-East Europe and Former Soviet Union - Shatokha, Volodymyr (European Journal of Sustainable Development, 2017)
Comparative analysis of iron & steel industry's transition in the countries of Central-East Europe as well as in Kazakhstan, Russia and Ukraine during the quarter of century after collapse of Soviet Union has been performed. Influence of political and socio-economic aspects on pathways and results of reform analysed focusing on restructuring, modernisation, production and consumption patterns, international trade etc. Energy efficiency and environmental performance indicators achieved in the countries concerned have been studied in the context of economic and environmental sustainability. Policies for greenhouse gases emissions abatement in the iron & steel sector have been analysed towards addressing commitments to Paris Agreement and further transition to a low-carbon and sustainable economy in the countries covered by this study. Keywords: Transition, sustainability, iron and steel industry